HLA-G polymorphism impacts the outcome of oral HPV infections in women - Jaakola Anna; Roger Michel; Faucher Marie-Claude; Syrjänen Kari; Grénman Seija; Syrjänen Stina; Louvanto Karolina (BMC, 2022)
Backround
Human leukocyte antigen (HLA)-G may have an important role in the natural history of human papillomavirus (HPV) infection. Our aim was to evaluate the role of HLA-G in the outcome of genital and oral HPV infections in women.
Methods
Analyses included 306 women from the Finnish Family HPV-study and were followed-up for six years. Genital and oral samples were tested for 24 different HPV types with multiplex HPV genotyping. HLA-G alleles were determined through direct DNA-sequencing. Unconditional logistic regression was used to determine the associations between HLA-G genotypes and HPV infection outcomes.
Results
Ten HLA-G alleles were identified. Most common HLA-G genotypes were the wild type G*01:01:01/01:01:01 (31.3%) followed by G*01:01:01/01:01:02 (26.8%). G*01:01:01/01:01:01 genotype was associated with increased risk of oral HPV infections by any HPV type or single-type with OR=1.86 (95% CI 1.14-3.04, P=0.01) and 2.22 (95% CI 1.14-3.71, P=0.02), respectively. G*04:01+ allele and the G*01:01:01/01:04:01 genotype both protected from any and single oral HPV infections; OR=0.46 (95% CI 0.23-0.89, P=0.02) and 0.53 (95% CI 0.23-0.97, P=0.03), respectively. G*01:01:02/01:04:01 genotype increased significantly the risk of infertility and its treatments, with respective OR=5.06 (95% CI 1.22-21.02, P=0.03) and OR=9.07 (95% CI 1.22-39.50, P=0.03). Both HLA-G alleles and genotypes showed several significant associations with the outcomes of oral HPV infections, but none of them had any impact on the outcomes of genital HPV infections in these women.
Conclusions
The host HLA-G genotypes appear to impact the outcomes of oral HPV infections in women but have little if any effect on genital HPV status or infection outcomes.